Caracterización molecular de ácido desoxirribonucleico (ADN) del cysticercus tenuicollis. - Avila Rocha, Christian Geovanny (2021)
This research was carried out in the Province of Pichincha, in the Metropolitan Public Company of Rastro Quito. EMRAQ-EP, the objective was to perform the genetic typing ofL Cysticercus Tenicollis. Cysts were collected in the post-mortem review of 20 slaughtered sheep, of both sexes, from several cities in the Ecuadorian highlands. The study population was a total of 186 sheep, of which 20 animals tested positive for Cysticercus Tenuicollis, giving us a frequency of 12.90% of the study population. The vesicles that were found in the epliplon and liver of each of the animals that were inspected were collected, which were prepared in the Laboratory of the Technical University of Cotopaxi, the same that were placed in a 1.5 ml tube with 1 ml 70% ethanol. For molecular typing, the cyst head is sent to the UDLA Research Laboratory, in a 1.5ml tube with 1ml of 70% ethanol to guarantee the integrity of the biological sample. It was determined that of the 20 samples recognized morphologically as Cysticercus Tenuicollis, the 20 were positive for the parasite in question by band amplification, which represents 100% molecular specificity, thus demonstrating that the use of PCR is more sensitive and reliable.